Peran Otoritas Jasa Keuangan Dalam Menjaga Stabilitas dan Keamanan Sistem Keuangan - Rizki Dwianto; Handoko Wahyu Utama; Ficky Desra Saputra; Gunawan Adi Wijaya; Fitri Aisyah; Endang Kartini (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
OJK is the institution responsible for overseeing and regulating the financial services sector, including banking, the non-bank financial industry, non-financial corporations, households, financial markets, and financial market infrastructure. OJK has an important role in monitoring developments in the condition of the financial system, identifying, analyzing and assessing existing risks. In addition, OJK is also tasked with providing and conveying the necessary data and information and is responsible for the accuracy of the data and information submitted. Through strict supervision, strengthening financial system infrastructure, and preventive measures, OJK plays a role in ensuring the stability and security of Indonesia's financial system.